The Small Bang - (:unkn) unknown (My University, 2023)
Species are often the most diverse at their origins, and all modern humans can trace their origins back to Africa. Our ability to communicate through language defines us; every human being speaks (or signs) at least one language. We may never know when our current forms of language were first spoken, or what speakers sounded like, but we can be assured that primordial languages were spoken in Africa. Yet, a paradox presents itself with respect to the apparent lack of linguistic heterogeneity in Africa: the languages comprise only four of the world’s more than 150 families. Isolates, languages with no known living relatives, represent the missing links between today’s homogeneity and the past’s diversity. Bangande, speakers of language isolate Bangime, are a unique community living in a remote area of Mali in West Africa. The Bangande are exceptional among African communities because their linguistic and genetic ancestry has thus far eluded scientific attempts to associate them with other languages and peoples. In fact, the Bangime language may represent the only confirmed language isolate spoken today in interior West Africa. In turn, the Bangande people have resisted genetic admixture with neighboring populations for upwards of 9.000 years. The root of their eponym [bang-], actually translates to ‘hidden’ or ‘secret’ in surrounding Dogon languages whose linguistic and genetic ancestors are almost as mysterious. The goal of this talk is to exhibit how our findings to date concerning the purported origins of the Bangime language and its speakers, the Bangande, can impact our understanding of human evolution.
Keywords: African Research